Ageing: Opportunity for a medicine in search for goals - Boitte, Pierre (Acta Bioethica, 2001)
Ageing and geriatric care constitute two aspects (collective and individual) of the same social and cultural reality, and should motivate medicine towards a healthy transformation of its practice, therefore becoming more aware of its own limitations and goals. Also becoming more appropriate for convincing society to accept ageing; a society which willingly would delegate medicine certain social and political tasks, even though they are not medical issues. This is the main idea sustained in this text.